Incredible edible science : recipes for developing science and literacy skills - Plaster, Liz.; Krustchinsky, Rick. (St. Paul, MN : Redleaf Press, 2010)
From the Publisher: Making learning exciting for children, Incredible Edible Science includes over 160 hands-on, food-based science activities with a strong literacy connection. The book provides everything needed to teach important science process skills in a safe, developmentally appropriate way. These cross-curricular activities promote brain development and fully engage children through physical involvement-such as exploring balance and texture as they create popcorn ball structures, classifying and patterning different types of cereal, and investigating fractions with biscuits-and participation in literacy and language components such as phonemic awareness, vocabulary development, and following directions. After the activity is complete, children can eat their work!
1. Food for thought -- Early brain development -- Science and young children -- The science, language, and literacy connection -- Social-emotional development and young children -- 2. Setting the table for learning -- Starting out strong: communicating with others -- Cooking safety and health -- Materials and equipment -- Snack centers -- The role of the teacher -- 3. Cooking up basic science process skills -- Six basic science process skills -- Observing/sight activities -- Observing/smell activities -- Observing/taste activities -- Observing/touch activities -- Observing/sound activities -- Classifying activities -- Communicating activities -- Measuring activities -- Inferring activities -- Predicting activities -- 4. Blending language and literacy into science activities -- Recipe for mixing literacy into science activities -- Recipe for teaching an integrated activity -- Guidelines for the reading experience -- Science/literacy activities -- Appendix A. rebus recipe art -- Appendix B. science process and skills alignment chart for chapter 3 activities -- Appendix C: science process and math skills alignment chart for chapter 4 activities.
Includes bibliographical references (page 243).
Keywords: Science -- Study and teaching (Early childhood) -- Activity programs; Language arts (Early childhood) -- Activity programs; Food -- Study and teaching (Early childhood) -- Activity programs; Cooking -- Study and teaching (Early childhood) -- Activity programs